Next-Generation Membrane Materials: Advances, Applications, and Challenges - V. Basil Hans (International Journal of Membranes, 2025)
Advanced membrane materials are better than regular polymers because they are more selective, permeable, and stable. New developments in nanomaterials, composite membranes, and surface engineering are making it possible to do more with water purification, gas separation, biomedical applications, and energy systems. Membrane technologies have become important tools in many areas, including biomedicine, energy systems, gas separation, and water purification. Recent progress in material science has made it possible to create next-generation membrane materials that are more selective, permeable, and long- lasting. This review looks at the newest membrane materials, such as thin-film nanocomposites, mixed matrix membranes, metal-organic frameworks (MOFs), covalent organic frameworks (COFs), and anodic aluminium oxide (AAO) structures. These new materials work better because they have better antifouling qualities, mechanical strength, and chemical resistance. The study looks at how new technologies in nanostructuring, surface functionalisation, and hybridisation are getting around the problems that have always been there in desalination, CO₂ capture, medication delivery, and fuel cells. The report also talks about important problems like scalability, long-term stability, and cost, and it talks about future research possibilities including bioinspired designs and AI-assisted membrane optimisation. The use of new materials and fabrication methods together is a major change in membrane research that will have a big impact on sustainable technologies and global resource management.
Keywords: Gas Separation; Nanocomposite membranes; and membrane technology are some of the keywords; desalination; metal-organic frameworks (MOFs); mixed matrix membranes